2020
DOI: 10.1016/j.ejogrb.2020.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis and inflammatory bowel disease: A systematic review of the literature

Abstract: Background: Irritable bowel disease and endometriosis are two common diseases characterized by chronic inflammation state and recurrent abdominal pain. As consequence of sharing of symptoms and of chronic inflammation, endometriosis and IBS may coexist and be misdiagnosed and this leads to delays in diagnosis, mismanagement, and unnecessary testing. In recent years, some studies have found higher risk of IBS in women with endometriosis, compared to women without endometriosis. Aims: To provide a general overvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 52 publications
3
36
0
Order By: Relevance
“…Regarding the potential differences between Italy and China overall in terms of incidence of comorbidities, according to the current relevant literature there are no significant differences between the two population in terms of baseline incidence of autoimmune, inflammatory, and metabolic diseases [33,34]. Besides, data on comorbidities among Italians are consistent with figures reported in already published studies on endometriosis [5,[35][36][37][38]. The different distribution of comorbidities with endometriosis in the two population suggested a different spectrum of diseases under different society and culture.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Regarding the potential differences between Italy and China overall in terms of incidence of comorbidities, according to the current relevant literature there are no significant differences between the two population in terms of baseline incidence of autoimmune, inflammatory, and metabolic diseases [33,34]. Besides, data on comorbidities among Italians are consistent with figures reported in already published studies on endometriosis [5,[35][36][37][38]. The different distribution of comorbidities with endometriosis in the two population suggested a different spectrum of diseases under different society and culture.…”
Section: Discussionsupporting
confidence: 74%
“…A better identification of systemic comorbidities should be taken into account in Italian group, because of the presence of a multidisciplinary team-including an immunologist, a gastroenterologist, a psychiatrist, a dietician, a neurologist, a pain specialist and a physical therapist-in the Italian Endometriosis centers. However, figures from Italians are absolutely in line with those reported in studies on cohorts from all over the world on women with endometriosis [5,[35][36][37][38]. A better investigation on systemic comorbidities among Chinese may be desirable in order to identify potential diseases accompanying endometriosis, in order to better explain clinical presentation and to plan a fully comprehensive treatment [39].…”
Section: Discussionsupporting
confidence: 61%
“…Limited research has assessed IBD and endometriosis. 16 A cohort study within the Danish National Hospital Register observed an increased risk of IBD for women with endometriosis compared to women without; however, this study lacked control for confounding factors. 17 Additionally, a survey of the Endometriosis Association members from the United States and Canada reported a higher prevalence of SLE, RA, MS, and Sjogren's syndrome among endometriosis patients compared with the general female population.…”
Section: Multivariableadjusted 1 or (95% Ci)mentioning
confidence: 99%
“…Although based on a small number of participants with SLE, IBD, or RA, we observed similar results to previous studies of a positive association between SLE, IBD, or RA and endometriosis. [12][13][14][15][16] A recent meta-analysis reported an increased likelihood of multiple autoimmune diseases, including SLE, RA, MS, and Sjogren's syndrome, among women with endometriosis compared to women without endometriosis. 4 However, it is important to note that the majority of previous studies have compared the risk of developing an autoimmune disease among women with and without endometriosis,…”
Section: Multivariableadjusted 1 or (95% Ci)mentioning
confidence: 99%
“…Bowel symptoms can include constipation, diarrhea, bloating, nausea, vomiting, dyschezia, and blood in the stool (6,7). To add further burden, women with endometriosis often demonstrate other co-morbid conditions [e.g., cardiovascular disease, autoimmune diseases (including rheumatoid arthritis, Crohn's disease, and ulcerative colitis), irritable bowel syndrome and cancer; (7)(8)(9)(10)]. Previous studies suggest that allergic diseases, including atopic conditions such as asthma and rhinitis, and food hypersensitivities are associated with endometriosis (11,12).…”
Section: Introductionmentioning
confidence: 99%